2021
DOI: 10.2147/ppa.s319193
|View full text |Cite
|
Sign up to set email alerts
|

Dental Fear and Patient Preference for Emergency Dental Treatment Among Adults in COVID-19 Quarantine Centers in Dammam, Saudi Arabia

Abstract: Purpose Dental fear is associated with the avoidance of dental visits and negative oral health outcomes. It is important to assess distribution of dental fear and preference for emergency dental treatment among adult population during COVID-19. Therefore, the purpose of this study was to evaluate dental fear and emergency dental treatment among adults in COVID-19 quarantine centers in Greater Dammam, Saudi Arabia. Materials and Methods Male and female adults (N=606) in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 35 publications
2
24
0
Order By: Relevance
“…Patients in this study mostly only visited dentists when they had a dental emergency. These results correspond with a study in the literature with similar findings, mainly due to fear of contracting the virus [15]. The anxiety of the patients visiting the dental clinics primarily depends upon the use of precautionary measures being followed by the dental staff.…”
Section: Discussionsupporting
confidence: 90%
“…Patients in this study mostly only visited dentists when they had a dental emergency. These results correspond with a study in the literature with similar findings, mainly due to fear of contracting the virus [15]. The anxiety of the patients visiting the dental clinics primarily depends upon the use of precautionary measures being followed by the dental staff.…”
Section: Discussionsupporting
confidence: 90%
“…The overall risk of bias assessment of the included studies is presented in Tables S1 and S2 in Supplementary Materials. Five studies reported a moderate level of bias [21][22][23][24][25], while the remaining five studies showed low quality [26][27][28][29][30].…”
Section: Risk Of Biasmentioning
confidence: 98%
“…In surveys administered through online platforms (Table S1 in Supplementary Materials), all studies reported the survey design describing the target population or sample frame. For IRB approval and informed consent process, IRB approval was obtained by seven out of eight studies [21][22][23][24]26,29,30], informed consent was obtained by four studies [22,25,28,29], and data protection was reported by only one study [22], while it was not applicable by four surveys [21,23,27,29]. Development and pre-testing were performed by only two studies [22,30].…”
Section: Risk Of Biasmentioning
confidence: 99%
See 1 more Smart Citation
“…This is may be explained by the financial conditions of the patients and their awareness about the pandemic (Schwendicke, Krois, & Gomez, 2020). It seems like the gender and geographic location has an effect on the patients fear too, only one third of the participants in another study accepted to seek dental care during the Covid-19 pandemic as related in a recent study destinated for 606 participants (Nazir et al, 2021) On the other hand, both groups feel satisfied and safe with the professionals PPE which was indicated by the WHO and diverse national and international authorities basing on studies tried to explain the relevance and function of each equipment (Jurema et al, 2020;Pan et al, 2020), as well-established infection control is the viable proposal for current and future pandemics (Schlenz et al, 2021). This finding agree with the outcomes of another study that reported a high acceptance In question 4, which was only destinated for the participants of groups 2, it was found that 59.81% of the participants do not feel insecure with the cross contamination caused by SARS-CoV-2 in collective health care units.…”
Section: Discussionmentioning
confidence: 98%